2014至2015年江苏省血液科病房病原菌分布及耐药状况的多中心回顾性研究 (Zhonghua Xue Ye Xue Za Zhi, 2017)
OBJECTIVE: To describe the distribution and drug resistance of pathogens at hematology department of Jiangsu Province from 2014 to 2015 to provide reference for empirical anti-infection treatment. METHODS: Pathogens were from hematology department of 26 tertiary hospitals in Jiangsu Province from 2014 to 2015. Antimicrobial susceptibility testing was carried out according to a unified protocol using Kirby-Bauer method or agar dilution method. Collection of drug susceptibility results and corresponding patient data were analyzed. RESULTS: The separated pathogens amounted to 4 306. Gram-negative bacteria accounted for 64.26%, while the proportions of gram-positive bacteria and funguses were 26.99% and 8.75% respectively. Common gram-negative bacteria were Escherichia coli (20.48%), Klebsiella pneumonia (15.40%), Pseudomonas aeruginosa (8.50%), Acinetobacter baumannii (5.04%) and Stenotropho-monas maltophilia (3.41%) respectively. CRE amounted to 123 (6.68%). Common gram-positive bacteria were Staphylococcus aureus (4.92%), Staphylococcus hominis (4.88%) and Staphylococcus epidermidis (4.71%) respectively. Candida albicans were the main fungus which accounted for 5.43%. The rates of Escherichia coli and Klebsiella pneumonia resistant to carbapenems were 3.5%–6.1% and 5.0%–6.3% respectively. The rates of Pseudomonas aeruginosa resistant to tobramycin and amikacin were 3.2% and 3.3% respectively. The resistant rates of Acinetobacter baumannii towards tobramycin and cefoperazone/sulbactam were both 19.2%. The rates of Stenotrophomonas maltophilia resistant to minocycline and sulfamethoxazole were 3.5% and 9.3% respectively. The rates of Staphylococcus aureus, Enterococcus faecium and Enterococcus faecalis resistant wards vancomycin were 0, 6.4% and 1.4% respectively; also, the rates of them resistant to linezolid were 1.2%, 0 and 1.6% respectively; in addition, the rates of them resistant to teicoplanin were 2.8%, 14.3% and 8.0% respectively. Furthermore, MRSA accounted for 39.15% (83/212). CONCLUSION: Pathogens were mainly gram-negative bacteria. CRE accounted for 6.68%. The rates of Escherichia coli and Klebsiella pneumonia resistant to carbapenems were lower compared with other antibacterial agents. The rates of gram-positive bacteria resistant to vancomycin, linezolid and teicoplanin were still low. MRSA accounted for 39.15%.